WACANA IKLAN HONDA SCOOPY DAN YAMAHA MIO FINO DALAM SURAT KABAR BALI POST - Juniastuti, Ni Luh Erna (Humanis, 2013)
Macro structure analysis is based on words, phrases, and sentences used in the ad. Gender analysis carried out ini advertising Honda Scoopy and Yamaha Mio Fino is viewed in terms of the selection of commercials that influence style that is used in the ad. Style here is different from the style of figurative language (figure of speech). Style is feminine or masculine.
Keywords: text , ad, and gender